Cybersecurity as an Essential Sustainable Economic Development Factor - Vasiu, Ioana; Vasiu, Lucian (European Journal of Sustainable Development, 2018)
Technological developments facilitated an impressive growth in international trade; however, organizations are facing numerous risks, resulting from their reliance on digital services and complex supply chains. One of the most notable risks concerns cybersecurity, which can take numerous forms and can have very significant negative consequences for the victims. This reality makes cybersecurity a major differentiator for organizations and an essential sustainable economic development factor. This paper employs an empirically-informed theoretical approach, and, based on a large corpus of data, consisting essentially of cases brought to courts, cybersecurity reports, and press releases, examines the main cybersecurity risks, grouped in three broad categories: damage, theft of trade secrets, and payment fraud. In each category, the main issues are illustrated with real case examples. The findings of this study underline the need for improved cybersecurity strategies, policies, and programs. The paper proposes a number of measures that must be taken, in order to provide conditions for a safer and better economic development environment. Keywords: Cybersecurity, E-Commerce, Sustainable Development, Damage, Trade Secret, Fraud, Loss